Purinergic P2X receptor 7 (P2X7R) inhibition induced cytotoxicity in glioblastoma - Matthew Drill; Liyen Katrina Kan; Richard P. Sequeira; Padmakrishnan Chorakode Jayakrishnan; Martin Hunn; Nigel C. Jones; Terence J. O’Brien; Mastura Monif (PLoS ONE, 2025)
Glioblastoma is the most common and aggressive form of primary brain cancer with a median survival of 15 months from diagnosis. The purinergic receptor P2X7 (P2X7R) is a regulator of several cell signalling pathways, and its expression is upregulated in glioblastoma. This study examined the expression and function of P2X7R in a human glioblastoma cell line, U251. We used a pharmacological antagonist of P2X7R, AZ10606120, to inhibit receptor function and delineate downstream consequences of receptor inhibition. Using RNA sequencing we demonstrated that P2X7R was expressed in the U251 cell line, harbouring both Y155H (Tyr to His) and E496A (Glu to Ala) single nucleotide polymorphism (SNP) mutations. The receptors functionality – namely its pore and channel conductance states were intact. Inhibition of P2X7R with small molecule antagonist AZ10606120, for 72 hours significantly decreased U251 cell number (p < 0.0001), and significantly increased tumour cell death, as evidenced by increased LDH release (p < 0.001). This reduction in tumour cell number was concentration-dependent, modelled by a least squares linear regression (R2 = 0.8221, IC50 = 17µM). The primary mode of cell death induced by AZ10606120 was shown to not be apoptosis, demonstrated through no significant changes in annexin V or cleaved caspase 3 staining in AZ10606120 treated cell versus control cells. Multiplex mRNA analysis demonstrated changes in genes associated with both apoptosis and pyroptosis, whilst a decrease in receptor-interacting serine/threonine-protein kinase 1 (RIPK1) expression along with an increase in TNFR1-associated death domain protein (TRADD) expression suggests potential involvement of the TRADD mediated RIPK1-independent necroptosis pathway. Collectively, this study describes several key characteristics of AZ10606120s acting as an anti-tumour small molecule pharmaceutical and highlights the potential of P2X7R inhibition as a novel therapeutic target in glioblastoma.